Dust temperature and time-dependent effects in the chemistry of photodissociation regions. Issue 2 (12th April 2019) - Esplugues, G; Cazaux, S; Caselli, P; Hocuk, S; Spaans, M
Abstract: When studying chemistry of photodissociation regions (PDRs), time dependence becomes important as visual extinction increases, since certain chemical time-scales are comparable to the cloud lifetime. Dust temperature is also a key factor, since it significantly influences gas temperature and mobility on dust grains, determining the chemistry occurring on grain surfaces. We present a study of the dust temperature impact and time effects on the chemistry of different PDRs, using an updated version of the Meijerink PDR code and combining it with the time-dependent code Nahoon. We find the largest temperature effects in the inner regions of high G 0 PDRs, where high dust temperatures favour the formation of simple oxygen-bearing molecules (especially that of O2 ), while the formation of complex organic molecules is much more efficient at low dust temperatures. We also find that time-dependent effects strongly depend on the PDR type, since long time-scales promote the destruction of oxygen-bearing molecules in the inner parts of low G 0 PDRs, while favouring their formation and that of carbon-bearing molecules in high G 0 PDRs. From the chemical evolution, we also conclude that, in dense PDRs, CO2 is a late-forming ice compared to water ice, and confirm a layered ice structure on dust grains, with H2 O in lower layers than CO2 . Regarding steady state, the PDR edge reaches chemical equilibrium at early times (≲10 5 yr). This time is even shorter (<10 4 yr) for high G 0 PDRs. By contrast, inner regions reach equilibrium much later, especially low G 0 PDRs, where steady state is reached at ∼10 6 –10 7 yr.